The predictors of catheter-related bloodstream infections in patients undergoing hemodialysis: A single center experience. Issue 1 (January 2023) - Demirci, Recep; Sahtiyancı, Berrak; Bakan, Ali; Akyuz, Okan
Background: Here we aimed to investigate the predictors of catheter-related bloodstream infections (CRBSI) in patients with acute kidney injury or chronic kidney disease who required renal replacement therapy through a non-tunneled hemodialysis catheter. Methods: A total of 111 patients who received non-tunneled hemodialysis catheters were retrospectively evaluated. Patients were divided into two groups; those who developed CRBSI and those who did not. Patient's demographic data, laboratory results at admission, information regarding catheter infections, and culture results were obtained from electronic medical records. Results: The mean age of the patients was 64 ± 16 years, and 51 of them were male. CRBSI occurred in 14 patients (12.6%). Admission serum albumin level (OR: 0.119, 95% CI: 0.019–0.756, p  = 0.024), admission mean platelet volume (OR: 2.207, 95% CI: 1.188–4.100, p  = 0.012) and catheter duration (OR: 1.580, 95% CI: 1.210–2.064, p  = 0.001) were independent predictors for the CRBSI development. ROC curve analysis demonstrated that a catheter duration of 22 days was predictive for presence of CRBSI (78% sensitivity, 76% specificity, AUC: 0.825, 95% CI: 0.724–0.925, p  < 0.001). Conclusions: Prolonged catheter duration, low serum albumin, and high mean platelet volume independently predict the development of CRBSI in patients undergoing hemodialysis for acute kidney injury or chronic kidney disease.